DINAMIKA DESENTRALISASI : MENGKAJI INTERAKSI KOMPETISI PARTAI, INTEGRITAS PEMILU, DAN KUALITAS TATA KELOLA PEMERINTAHAN - Rita; Mustafa, Cecep (Bawaslu Provinsi Kepulauan Riau, 2023)
This essay aims to provide a comprehensive analysis of decentralization, party competition, and electoral integrity within the framework of institutional design theory. By examining the interplay between central governments, regional authorities, and political parties, we seek to enrich academic scholarship and offer practical insights for policymakers engaged in governance and policy-making. Our analysis employs a literature analysis to examine the impact of decentralization on party behavior, electoral processes, and governance quality. Our comprehensive analysis reveals several key findings. First, decentralization is not a one-size-fits-all phenomenon; it varies across regions and contexts, influenced by a range of factors. Second, an inclusive measure for assessing the risk of electoral defeat within a decentralized framework provides deeper insights into electoral dynamics. Third, the interaction between regional and national parties shapes regional party systems in decentralized settings. Fourth, political parties engage in rational cost-benefit calculations, affecting their decisions on electoral fraud. Most importantly, we find that decentralization can enhance the fairness of national elections by reducing the incentives for electoral fraud, ultimately strengthening electoral integrity and the quality of government. Our study bridges existing gaps in the literature and offers a comprehensive understanding of the complex dynamics inherent to decentralized governance structures. This research contributes valuable insights to academic scholarship and provides practical guidance for policymakers navigating the challenges and opportunities presented by decentralization in contemporary elections.